THE ROLE OF DIGITAL LITERACY AND LEARNING MOTIVATION ON STUDENTS’ CRITICAL THINKING - Uum Sri Utami; Nurrohmatul Amaliyah (Universitas Bina Bangsa Getsempena, 2025)
This study aims to examine the role of digital literacy and learning motivation in students' critical thinking skills. This study employed a quantitative approach using a correlational design. The fourth-grade students at several public elementary schools in the Pegadungan subdistrict were selected as the sample of this research. The research sample consisted of 128 students. Data were obtained through tests measuring critical thinking skills and questionnaires assessing digital literacy and learning motivation. Data analysis was performed using multiple linear regression tests. The results showed a significant relationship between digital literacy (r = 0.331; p < 0.05) and learning motivation (r = 0.223; p < 0.05) with students’ critical thinking skills. Simultaneously, both variables had a positive and significant effect on students' critical thinking skills (R = 0.438; Sig. = 0.000). These findings indicate that students with higher levels of digital literacy and stronger learning motivation tend to demonstrate better critical thinking abilities. In conclusion, improving students’ access to digital resources and fostering intrinsic learning motivation can contribute significantly to the development of critical thinking skills. The findings of this study suggest that educators should integrate technology-based learning activities and motivational teaching strategies into classroom instruction to support the enhancement of critical thinking skills in elementary educatio